The relationship between financial development and economic growth: Evidence for South American economies - Becerra Hurtado, Juan Pablo (2023)
Within econometric analysis, financial development and economic growth are two issues of great importance for economic and social planning, these have usually been directly related, without considering other factors that affect this relationship. Therefore, this research studies the link between this relationship, adding variables such as savings, inflation, foreign direct investment, and gross capital formation. For this, data from official information sources such as the World Bank and the International Monetary Fund were used. To obtain results, panel-type econometric techniques were used, with cointegration estimates being precise, such as Westerlund (2005) and (2007), and long-term chance such as Dumistrecu y Hurlin (2012). We found that the variables as a whole maintain a convergence relationship, with financial development being a determinant of economic growth in most countries, with savings and gross capital formation being the factors that drive this relationship.